Effect of External Counterpulsation on Exercise Recovery in Team Sport Athletes - Collins, Ruben; McGrath, Denise; Horner, Katy; Eusebi, Silvia; Ditroilo, Massimiliano (International Journal of Sports Medicine, 2019)
External counterpulsation (ECP), an electrocardiogram-led sequential compression of lower limbs, has been recently proposed for sports recovery, but research is scant. This study examined the effects of an ECP session upon neuromuscular function (vertical jump and torque/velocity characteristics), biochemical responses (creatine kinase, cortisol, testosterone, alpha-amylase and immunoglobulin-A), and muscle soreness (visual analogue scale) following high-intensity exercise. Twenty-one male team sport athletes (age: 21.6±3.4 yrs; height: 182.7±7.3 cm; body mass: 82.7±9.3 kg) recovered from the fatiguing exercise using either ECP or rest. Data collection was conducted at three separate time points: upon arrival (Pre), post-recovery (Post), and 24 h post-recovery (24hPost). Significant main effects for time were observed for increased torque/velocity slope and for decreased isometric extension peak torque (p<0.001). Significant main effects for time were observed for increased creatine kinase, testosterone, alpha-amylase, and muscle soreness (all p<0.001). Significant interaction effects were observed at post-testing following ECP: Cortisol release and the related decline in testosterone/cortisol ratio were attenuated, and immunoglobulin-A was increased following ECP in comparison to the control (all p<0.05). Following high-intensity exercise, ECP has potentially beneficial effects upon biomarkers of recovery, without affecting the neuromuscular function.
Keywords: fatigue; biomarkers; muscle soreness; peak power; torque/velocity relationship; countermovement jump